The impact of bank loan terms on intangible investment in Europe - Matthieu Segol; Atanas Kolev; Laurent Maurin (European Investment Bank (EIB), 2021)
Firm investment, Intangible assets, Loan terms, Credit constraint, Survey data, Instrumental variable approachUsing European firm-level data from a new survey, the EIBIS, we document the effect of bank loan terms on investment in intangible assets of non-financial corporations. We show that quantity rationing is a primary determinant borrowers' propensity to invest in intangible assets. Provided that firms are satisfied with their loan size; unfavorable rate, maturity and collateral requirements have no significant effects on the probability to invest in intangible assets. These terms however, do have a negative impact on the probability to invest in multiple intangible assets, undermining the ability of firms to benefit from the complementarities of these assets. We document the effect of loan conditions on investment intensity, as well. The effect of quantity rationing on the amount invested in intagible assets is found to be limited. Other loan conditions however, like cost, maturity and collateral requirements, have significant effect on investment intensity.
Keywords: G21; D82; O30; H81; C35; 330; Firm investment; Intangible assets; Loan terms; Credit constraint; Survey data; Instrumental variable approach